Best Practices for Counseling Clients Experiencing Poverty: A Grounded Theory. (8th June 2020) - Clark, Madeline; Ausloos, Clark; Delaney, Colleen; Waters, Linda; Salpietro, Lena; Tippett, Hannah
Abstract : Poverty is a pressing sociopolitical issue in the United States and worldwide. Poverty experiences have a significant effect on one's mental health and overall wellness. Therefore, the ability to effectively serve clients experiencing poverty is critically important to professional counselors. However, there are no empirical models for counseling clients experiencing poverty. The authors present the results of a constructivist grounded theory study in which 21 professional counselors who work with clients experiencing poverty were interviewed to identify best practices for working with this population. Five major best practices are identified: (a) awareness, (b) training, (c) knowledge, (d) skills, and (e) advocacy. Implications for professional counseling are included.